The Urgency of Death Penalty Implementation for Corruptors on Corruption Social Assistance Fund in Indonesia - Bagas Satria Wicaksono (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2022)
The criminal law system is never separated from the legal values ??themselves. Starting from Pancasila to the 1945 Constitution, Article 3 paragraph 1 emphasizes that Indonesia is a state of law, so whatever the law is, it is the law that must be resolved. Like corruption, which from time to time is getting worse. The weakening of the regulation of capital punishment for corruptors is so lacking that it does not give rise to the principles of justice, expediency, and certainty. Injustice in law can and must be denied to form and have a legal character. Especially for the perpetrators of corruption in social assistance funds in Indonesia. The focus of the problems studied in this study are: 1). How is the Death Penalty Arranged for Corruptors in the Indonesian Criminal Law System? 2). Is the Implementation of the Death Penalty for Corruptors of Social Assistance Funds in Indonesia in accordance with Legal Values? 3). What is the Urgency of Implementing the Death Penalty for Social Assistance Fund Corruptors in Indonesia in the Future? As a means of supporting this research in identifying these problems, this research uses normative juridical analysis with library research. This research concludes: 1) the laws and regulations governing the eradication of corruption, Law no. 20 of 2001 regulates the death penalty in its law only in Law no. 31 of 1999, 2) Starting from the point of view of the death penalty for corruptors in terms of the value of legal certainty, the value of expediency, the value of legal justice, 3) To predict and apply the death penalty for perpetrators of corruption in Indonesia, it is necessary to compare the application of the death penalty in several other countries. China, Vietnam, Thailand.